Unconstitutionality of Urgency Decree No. 016-2020 - Yangali Iparraguirre, Gino Ernesto (2020)
The purpose of this work will be to warn the reader about the various contradictions that the Executive Power and its promoting entity (National Civil Service Authority [SERVIR]) have incurred, by improperly conditioning the functions, jurisdiction and the interpretation that the Judicial Power must make about the claims of recognition of an indefinite term employment relationship, the replacement of the job and compensation for damages. This problem is created by not taking into account that there are various public servants who are not contained within the case of «Huatuco Huatuco», a legal precedent, since they have been excluded through various interpretations made by the Supreme Court of Justice of the Republic and by the Constitutional Court itself (about which it will be detailed later). Therefore, it is necessary that the entire legal community reflect on the constitutionality of the Emergency Decree No. 016-2020, while limiting the replacement mandate, its prior legislative admission, the renewal of the claim and the prohibition of accumulation. They would find themselves contravening various fundamental rights, such as adequate protection against arbitrary dismissal, res judicata, effective judicial protection, access to justice and the prohibition of arbitrariness.